Pengembangan Potesi Ekonomi Lokal Daerah Untuk Mengurangi Kesenjangan Pertumbuhan Antar Kecamatan Di Kabupaten Sukoharjo Tahun 2010-2015 - Al Viana, Hendika; , Dr. Daryono Soebagyo.,MEc (2017)
This study aims to determine the numbers growing inequality between districts and to determine the sectors where the most potential to boost economic growth so as to reduce the rate of inequality in each district in Sukoharjo district during the period 2010-2015. This study uses secondary data, such as the GDP and the number of residents in the District / County. In this study will be used in the form of index analysis tool Williamson, Analysis Location Quotient, Shift-Share Esteban-Marquilas and Typology Klassen Sector Wide Approach. Based on the analysis that has been conducted, the results; Growing inequality is relatively high with IW value of 0.5388 in 2010 to 0.6582 in 2015. Based on the calculation of the District LQ Bendosari, Bulus, Nguter, Tawangsari and Weru is a relatively underdeveloped area because it has the leading sectors. District of Baki, Mojolaban, Polokarto, Kartasura has three leading sectors, District Sukoharjo has two key sectors, Grogol and Gatak has four leading sectors that have the potential to be developed. Shift-Share analysis results Esteban-Marquilas, each district of the period of observation changes the potential winning. Based on the typology analysis Klassen uses the value of shift-share (Cij) combined with the value of LQ, an area that has agriculture as a sector superior the District Bendosari, Mojolaban, Polokarto, Tawangsari and Weru, an area that has the mining and quarrying sector as a sector superior is the District Mojolaban and Polokarto. Areas that had featured sector of the manufacturing sector among others the District Baki, Gatak, Kartasura, Mojolaban, Nguter and Tawangsari. The leading sectors of electricity, gas and water supply is owned by Grogol and Kartasura the leading sectors of the building owned by the District Baki, Gatak, Nguter, Polokarto, Sukoharjo and Tawangsari. Areas that have a trade, hotels and restaurants as superior sector, among others, the District Baki, Grogol, Kartasura, and Tawangsari, seed transport and communications sector is owned by the District Baki, Feathers, Grogol, Kartasura, and Weru. Areas that had featured sector of the financial sector, rents and services of the company include the District Kartasura and Sukoharjo, the last seed sector is the services sector which is owned by the District Bendosari, Grogol, and Kartasura.